ANALYSIS OF SCIENTIFIC RESEARCH IN THE FIELD OF SCIENCE “PUBLIC ADMINISTRATION” IN THE DIRECTION OF ENSURING SUSTAINABLE DEVELOPMENT IN UKRAINE - Khymchak , V. (Theory and Practice of Public Administration, 2020)
The Public Administration Reform Strategy for 2016-2020, approved by the Government on June 24, 2016 and incorporating an appropriate plan of measures for its implementation, has been updated the state of affairs in the public administration system conducted by the experts of the European SIGMA Program (Support for Improvement in Governance and Management, a joint initiative of the OECD and the EU), as well as their recommendations. The implementation of this Strategy is aimed at building a system of public administration that will be effective and accountable to citizens and that will work in the public interest on the basis of ensuring the sustainable development of the country.At the same time, this requires a scientific and theoretical justification for the formation of effective mechanisms for ensuring sustainable development in the public administration system in Ukraine, which in turn provides for the analysis of scientific research in the field of public administration in the direction of ensuring sustainable development in Ukraine.Various aspects of ensuring sustainable development are highlighted in the writings of Ukrainian scientists, who investigated the mechanisms of public administration in the field of science “Public Administration”.The article analyzes the scientific research of scientists in the field of public administration in the direction of ensuring sustainable development in Ukraine. According to the results of the analysis, the following mechanisms can be distinguished among the mechanisms of public administration researched by scientists in this field in the context of sustainable development: public administration of sustainable development in the regions (on the basis of the regional and cross-border cooperation); state management of sustainability in the regional ecological and economic systems; regulation of gross regional product as a factor of sustainable development in the region; ensuring sustainable development of the territorial community; regulation of balanced development in the utility services sector; optimization of public administration in the conditions of sustainable development; leading public administration.